2012
DOI: 10.1111/j.1467-7660.2012.01787.x
|View full text |Cite
|
Sign up to set email alerts
|

The Expansion of Industrial Tree Plantations and Dispossession in Brazil

Abstract: The recent expansion of tree plantations is the most important agrarian change in many parts of Brazil. This article uses the results of extensive field research to analyse the different ways paper and pulp companies assure their land base for eucalyptus plantations. The mechanisms of land access have changed little over the decades, amounting to a process of primitive accumulation which seems to be controlled by the ways the pulp industry influences land markets and prices, the strength of any resistance, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
12

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 24 publications
0
23
0
12
Order By: Relevance
“…Especially, Brazil and Uruguay have been attracting foreign investment during the past ten years, but during more recent years, there has been an increasing interest especially toward other Latin American countries such Colombia, Panama, Ecuador and Paraguay Flynn and Pahkasalo, 2015). For private forest product companies, the timberland ownership remains the most preferred option in many areas with high land returns such as Brazil (Kröger, 2012), even though the competition for arable land and increased land prices have led to a search for alternative strategies for organizing forest ownership in emerging areas. As an example, outgrowers schemes in which industrial buyers make contracts with local farmers have become increasingly popular in many developing regions (see Desmond and Race, 2000;Cossalter and Pye-Smith, 2003).…”
Section: Vertical Integration In Global Forest Sectormentioning
confidence: 98%
See 1 more Smart Citation
“…Especially, Brazil and Uruguay have been attracting foreign investment during the past ten years, but during more recent years, there has been an increasing interest especially toward other Latin American countries such Colombia, Panama, Ecuador and Paraguay Flynn and Pahkasalo, 2015). For private forest product companies, the timberland ownership remains the most preferred option in many areas with high land returns such as Brazil (Kröger, 2012), even though the competition for arable land and increased land prices have led to a search for alternative strategies for organizing forest ownership in emerging areas. As an example, outgrowers schemes in which industrial buyers make contracts with local farmers have become increasingly popular in many developing regions (see Desmond and Race, 2000;Cossalter and Pye-Smith, 2003).…”
Section: Vertical Integration In Global Forest Sectormentioning
confidence: 98%
“…Toppinen et al (2010), for example, explained how the increase in market demand and the availability of fast-growing forest plantations had especially driven pulp and paper sector firms to relocate their production from a developed country base to Asian and Latin American countries where crop rotation periods are typically much shorter. Simultaneously, the effects of establishment of fast-growing plantations on natural forests has been in particular dividing the opinions of the forest industry, local communities and Non-Governmental Organizations (see Vihervaara and Kamppinen, 2009;Gerber, 2010;or Kröger, 2012). Fernholz et al (2007) concluded that forest product companies have been forced to reevaluate the role of their forests as a strategic asset.…”
Section: Introductionmentioning
confidence: 97%
“…The transfer of the governance of government minority holdings in companies to the holding company Solidium Ltd in 2007 intended to make an end to all politics as concerns these companies. However, the international business operations of some of these companies have continued to implicate the Finnish government both among national and foreign scholars and political activists (Myllylä and Takala , Kröger ). Within Finland, the elevated management compensation in some of the companies in which the government has minority holdings in emulation of general global models (see, for instance, Shin ) has evoked criticism even among some of those political decision‐makers who originally introduced the compensation schemes (Ranki ).…”
Section: The Institutional Forms Of Governance Towards National Govermentioning
confidence: 99%
“…; Rudorff et al . ) – and Eucalyptus – used for paper production (Kröger ) – are two of the main plantations that are expanding rapidly over vast areas. These plantations may differ in their degree of permeability to individual movements between fragments (Renjifo ; Anderson et al .…”
Section: Introductionmentioning
confidence: 99%